RAGAM EKSPRESI BERAGAMA: AGAMA DALAM PERSPEKTIF SOSIOLOGI - Toguan Rambe; Seva Maya Sari; Nurhayani Rambe (UIN Sumatera Utara Medan, 2021)
Abstrack Religion is understood as a universal phenomenon in human life as a whole, from the primitive to the ultra-modern, with such conditions humans are often defined as religious creatures. In a sociological perspective, religion is seen as a belief system that is manifested in certain social behaviors related to human religious practice. So that every behavior he plays will be related to the belief system of the religious teachings he adheres to. Human religious behavior in social studies is played by the strength of the values of religious teachings that were internalized before. This study uses a sociological approach to religion which is understood from a sociological perspective as a social phenomenon displayed by humans and community groups. Religion and religious behavior grow and develop from a sense of human dependence on supernatural powers which they feel as a source of life. Therefore, in a sociological perspective, there are several efforts and aspects that are very important in religion, namely: Belief (Religious Belief, Ritual and Ceremony (Religious Ritiual), Personal Experience (Religious Experience), Moral Community (Religious Community). The purpose of this study is to understand social phenomena related to various human expressions in religion, both in worship and muamalat. The importance of a sociological approach in understanding religion can be understood because there are many religious teachings related to social problems, so this study is a contribution and solution to the social problems of religious communities. Keywords: Expression, Religion and Sociology.